TVECM TO ANALYZE THE RELATIONSHIP BETWEEN NET FOREIGN ASSETS AND CURRENCY CIRCULATION - Ana, Chantika Putri; Lestari, Trianingsih Eni; Permadi, Hendro (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
In the analytical balance sheet of the base money monetary authority, Bank Indonesia explained that net foreign assets (NFA) affected the circulation of base money, including currency. This gives an assumption regarding the indication of a causal relationship between currency circulation and NFA. In addition to the causality test, the primary purpose of this study is to identify long-term equilibrium relationships between NFA and Currency Circulation. The cointegration test obtained r = 1, indicating cointegration (long-term equilibrium). Time series data plots of these two variables tend to have a trend and are not stationary. The Vector Error Correction Model (VECM) is applied as an analytical method used to correct long-term relationships between variables that are not stationary. However, in the concept of VECM deviation and short-term dynamics, the association is assumed to be linear. At the same time, in applying economics, the relationship between economic variables is not necessarily linear. The significance test for the presence of a threshold using a fixed regressor bootstrap shows a threshold effect or nonlinear VECM, so it is necessary to use an analytical method that can combine nonlinearity and cointegration through the Threshold Vector Error Correction Model (TVECM). In this study, modeling of TVECM 2 regimes and three regimes were carried out. TVECM 3 regimes obtain the best model with two threshold values ​​of -310850 and -260156.